The Effect of Canva-Assisted Problem Based Learning Model to Improve Learning Outcomes: A Case on Data Presentation - Rivai, Sri Pujawati; Pomalato, Sarson W. Dj.; Achmad, Novianita (IKIP Siliwangi, 2025)
Mathematics is an important subject as it enhances critical thinking, problem-solving skills, and contributes to the advancement of science and technology. However, many students perceive it as a difficult subject, which hinders their interest and performance in learning mathematics. Traditional teacher-centered teaching methods and the lack of engaging learning media contribute to this issue. The purpose of this study is to examine the difference in learning outcomes between students taught using the Problem-Based Learning (PBL) model assisted by interactive media Canva and those taught using the Inquiry-Based Learning (IBL) model assisted by interactive media Canva, focusing on data presentation material in seventh-grade students at MTs. Negeri 1 Bone Bolango. This study employed an experimental research method with a Post-test Only Control Group Design. Two treatment groups were used: the experimental group and the control group. The research participants were 24 students from class VII.2 and 23 students from class VII.3. Data were collected through posttests. The intervention involved using the PBL model integrated with Canva as an interactive learning tool. The results were analyzed using paired sample t-tests to determine significant differences in learning outcomes. The results indicate a significant improvement in students' learning outcomes after the implementation of the PBL model with Canva assistance. The average posttest score increased from 52,17 to a higher value, suggesting better understanding and engagement. In conclusion, the use of the Canva-assisted PBL model effectively improves students' learning outcomes in mathematics, particularly in data presentation topics. This approach can serve as a valuable tool to promote active, student-centered learning in mathematics education.